Parental Health Literacy and Nutritional Practices as Predictors of Stunting Prevention in Rural Indonesia: A Rasch Analysis - Kurniawaty, Lia (Al-Athfal: Jurnal Pendidikan Anak, 2025)
Purpose – Stunting remains a critical threat to early childhood development, with impacts on both physical growth and long-term cognitive outcomes, yet prevention efforts remain uneven. This study examines the role of parental health literacy in translating nutritional awareness into consistent daily feeding practices to support stunting prevention.Design/methods/approach – This study used a descriptive survey design with Rasch analysis to examine parental health literacy and parental attention to children’s nutritional needs in the context of stunting prevention. The study involved 176 parents of young children in Sukabumi Regency, Indonesia, selected through random sampling. Questionnaire data were used as the main source of analysis, while observations and brief conversations with parents were used only as contextual support in interpreting the setting. Rasch modeling was employed to assess item functioning, reliability, separation, and the distribution of respondents and items on the same logit scale.Findings – The findings indicate that parents more readily endorsed general forms of nutritional concern than structured feeding practices requiring consistent regulation of meal portions and meal times. This suggests that parental health literacy functions as an enabling condition, but does not automatically translate into stable household practice. The Rasch results showed strong measurement performance, with person reliability of 0.93, item reliability of 0.99, Cronbach’s alpha of 0.94, person separation of 3.63, and item separation of 13.67. Taken together, the results point to a meaningful gap between nutritional awareness and the practical organization of everyday feeding routines, which is where prevention appears most vulnerable.Research implications/limitations – The findings indicate that the main challenge in stunting prevention lies not in parental knowledge alone but in the consistent enactment of household feeding routines, positioning health literacy within everyday caregiving practices and constraints. The study is limited by self-reported data and a cross-sectional design, which preclude causal inference and longitudinal verification of child growth outcomes.Practical implications – The results suggest that interventions should move beyond general nutrition awareness toward strengthening routine-based practices such as portion control, meal timing, and balanced diet planning. These insights inform policymakers, health educators, early childhood practitioners, and families in designing more actionable, context-sensitive prevention strategies at the household level.Originality/value – This study advances stunting research by analytically distinguishing parental health literacy from the practical regulation of children’s feeding routines. By applying Rasch analysis to map differential item difficulty, it reveals a critical gap between nutritional awareness and structured practice, offering a grounded perspective for family-based prevention in rural and Global South contexts.Paper type Research paper